2023
DOI: 10.1093/geroni/igad047
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Quality of Life: The Mediating Role of ADL, IADL, Loneliness, and Depressive Symptoms

Abstract: Background and Objectives The ubiquity of multimorbidity makes it crucial to examine the intermediary factors linking it with quality of life (QoL). The objective was to examine to what extent the association between multimorbidity and QoL was mediated by functional and emotional/mental health and how these mediation pathways differed by sociodemographic factors (age, gender, education, financial strain). Research Design and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
2
1
0
Order By: Relevance
“…In this study, the participants were 60 years and older, whereas Connolly's study focused on individuals aged >65 years. According to a previous study (24), age has been identified as an influencing factor of BADL among older adults, which aligns with the present study. Tissues and organs, including the brain, tend to exhibit signs of aging as a person grows older.…”
Section: Discussion the Prevalence Of Badl Disability In Older Adultssupporting
confidence: 92%
“…In this study, the participants were 60 years and older, whereas Connolly's study focused on individuals aged >65 years. According to a previous study (24), age has been identified as an influencing factor of BADL among older adults, which aligns with the present study. Tissues and organs, including the brain, tend to exhibit signs of aging as a person grows older.…”
Section: Discussion the Prevalence Of Badl Disability In Older Adultssupporting
confidence: 92%
“…The mediating effect model shows that ADLs have multiple mediating effects on the relationship between health behaviors and QOL, and the incidence of ADL restriction in older adults is negatively correlated with reported results on QOL, which is consistent to some extent with previous studies ( 29 ). At the same time, several previous studies have concluded that limited ADL capacity in older adults with advanced disease is significantly associated with QOL ( 8 , 41 , 42 ).…”
Section: Discussionsupporting
confidence: 90%
“…IADLs were assessed in this study using the Functional Activities Questionnaire (FAQ) ( 28 ), which consists of 10 items to assess whether respondents are able to perform the following activities independently: shopping, cooking, using communication tools, cleaning, washing, purchasing medicines, using public transportation, managing finances, working, and hobbies. Each items is scored on a 3-point scale, from 0 (normal or not done, but can do) to 3 (completely dependent on others); a higher FAQ score indicates worse function ( 29 , 30 ). The normal standard is less than 5 points; a score greater than or equal to 5 is an anomaly, indicating that respondents has difficulty being independent in their families and communities ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research indicated that different multimorbidity combinations were associated with differential risks of disability, measured by a combined ADL-IADL index [ 12 ]. Other studies also reported that both ADL and IADL were crucial intermediary factors on the pathway between multimorbidity and quality of life [ 45 , 46 ], and IADL was a key indicator in assessing the autonomy of community-dwelling older adults [ 35 ]. The current study explored the different care-receiving characteristics in ADL/IADL items associated with multimorbidity patterns, and could serve as a bridge between multimorbidity patterns and quality of life, for both care-recipients and caregivers.…”
Section: Discussionmentioning
confidence: 99%